2017
DOI: 10.15294/jpfi.v13i2.6592
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Questionnaire to Investigate Students� Attitudes and Approaches in Physics Problem Solving

Abstract: This study aims to develop physics problem solving survey utilized to obtain students attitude and approach while solving physics problem. Several steps are conducted to develop the survey: validating, computing reliability, and testing. This research involves Physics Education students-Tanjungpura University who study at Fourth and Sixth semester. Furthermore, after questionnaire administered to the students, data are analysed through determining average score of the students and computing average percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…The results showed that the students' attitudes and approaches were on average slightly positive (3.33 points of 5), which in this case means that they resembled more expert-like attitudes and approaches than novice-like ones. This result is in line with the previous studies (Balta, Mason & Singh, 2016;Mason & Singh, 2010, 2016Sirait, Sutrisno, Balta & Mason, 2017).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The results showed that the students' attitudes and approaches were on average slightly positive (3.33 points of 5), which in this case means that they resembled more expert-like attitudes and approaches than novice-like ones. This result is in line with the previous studies (Balta, Mason & Singh, 2016;Mason & Singh, 2010, 2016Sirait, Sutrisno, Balta & Mason, 2017).…”
Section: Discussionsupporting
confidence: 94%
“…This is an interesting result that should be examined more carefully with larger sample because several studies on mathematical problem solving suggest that male are better problem solvers than females (Gallagher et al, 2000). Moreover, the study by Sirait et al (2017) done in Indonesia showed that males were more expertlike when compared to females in terms of their attitudes and approaches in physics problem solving. One possible reason for this may be the fact that female university students in Turkey usually attend courses better, struggle more with homework assignments and accordingly better engaged with the problems and have higher grades (Personal observations).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The results of the study were found contrary to the researches ofBecker and Forsyth (1994), Astur, Purton, Zaniewski, Cimadevilla andMarkus (2016) andMefoh, Nwoke,Chukwuorji andChijioke (2017) showing that males possess more problem solving ability than females whereas the study of Cakir(2017) found that females possess more problem solving ability than males. The results of the present study are in conformity with the results obtained by Ajai andImoko (2015), Sebastian (2017) and Mason (2017).The study suggests that the gender have no significant bearing on the problem solvingability of the secondary students.…”
Section: Discussionsupporting
confidence: 92%
“…Mefoh, Nwoke, Chukwuorji and Chijioke( 2017) also corroborated the results of Astur, Purton, Zaniewski, Cimadevilla and Markus(2016) and found that male had significant advantage in solving problem as compared to the female.The study of Cakir(2017) found that problem-solving ability of female participants in the research was found to be higher than male participants.The study of Sebastian (2017) showed that male and female students have no significant difference in conceptual difficulties in problem solving but male students have higher computational understanding than female students in problem solving. Sirait, Sutrisno,Balta and Mason (2017) found that most of students have the same attitudes and approaches inproblem solving.Thus the results of most of studies are quite scattered and are in disagreement and need to relook it from the perspective of gender.…”
Section: Introductionmentioning
confidence: 92%